If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 = 6 + 5v Solving -9 = 6 + 5v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-5v' to each side of the equation. -9 + -5v = 6 + 5v + -5v Combine like terms: 5v + -5v = 0 -9 + -5v = 6 + 0 -9 + -5v = 6 Add '9' to each side of the equation. -9 + 9 + -5v = 6 + 9 Combine like terms: -9 + 9 = 0 0 + -5v = 6 + 9 -5v = 6 + 9 Combine like terms: 6 + 9 = 15 -5v = 15 Divide each side by '-5'. v = -3 Simplifying v = -3
| 3y+7=5y+1 | | 32x+(-32x+25)=12 | | 142,000,000/1.19 | | 12x-20=7x+20 | | f(20)=0.05x+3 | | 9c-4=26-c | | 50=5(3m-2) | | -15(-B)= | | 1/4=2/x | | -42=4t | | d/5-3=-4 | | 7+3t=5t-1 | | -0.6k-1+0.5k=3 | | g/10=10 | | 4x+-5y=-12 | | 276/6 | | 6c-3c+2d-4d= | | 2m+4=m-10 | | 0=x^2-20x+100 | | 5h/3=15 | | bxA=c | | 13x-6=4(3x+2)-2 | | 150,000,000/1.18=1.18N/1.18 | | y=42x+15 | | -33=2(v-6)-5v | | a+a.32=-325 | | (x+2)*(x+2)=14 | | -7x=6+3 | | 7/10=n/6 | | 3(m-2)=2(m+1)-3 | | 5/3u-1=-1/2u-1/2 | | 2=y+x+7 |